The Eastern and Western “Scriptures” for Postmodernity: Toward a Unified Ethos in Religion, Science, and Philosophy - Abraham, T. J. (Archīum Ateneo, 2015)
Postmodernism underscores the impossibility of discovering any truth. One can at best only construct a truth capable of ensuring optimal wellbeing for everyone. The traditional undifferentiated efforts of science, religion, and philosophy, which became compartmentalized in the Enlightenment, are again streamlined in postmodernity. A new ethics is the point of convergence for these three disciplines to fashion a sustainable universe. Yet Nagarjuna, who has long been overlooked, advocates a passage beyond language. It is an initiative that finds resonance in some postmodern masters as well.